Investigating the relationship between entrepreneurship and regional development: Case of developing countries - Ondřej Dvouletý; Alisa Gordievskaya; David Anthony Procházka (Journal of Global Entrepreneurship Research, 2018)
A lot has been written about the relationship between entrepreneurship and regional development in the past years. However, do we have conclusive empirical evidence for justification of this relationship? Policymakers expect from entrepreneurship positive impact on country's wealth and employment. Nevertheless, several scholars have argued that the impact of entrepreneurship might be even negative, especially, when the institutions are not working well. This might be a case of developing countries. According to our research, a recent empirical study that would be investigating this relationship is missing. Therefore, we utilize the dataset of 48 countries classified according to U.N. as developing for years 2000-2015 and we empirically test the relationship between the established business ownership rate (obtained from Global Entrepreneurship Monitor) and a set of country's economic indicators (Gross Domestic Product, Gross National Income, and Human Development Index). Obtained estimates support a hypothesis assuming a negative influence of entrepreneurship on regional development of developing countries (represented by GDP and GNI). Nevertheless, we failed to prove any impact of entrepreneurship on HDI. These findings have crucial implications for both policymakers and researchers. Based on this study, more efforts need to be put to better understand different forms of entrepreneurial activity in developing countries, its institutional context, and link towards regional economic development.
Keywords: L26; O12; 650; Entrepreneurship and regional development; Established business ownership rate; Developing countries; Harmful entrepreneurial activity